2022
DOI: 10.3389/fimmu.2022.875786
|View full text |Cite
|
Sign up to set email alerts
|

JMJD8 Is an M2 Macrophage Biomarker, and It Associates With DNA Damage Repair to Facilitate Stemness Maintenance, Chemoresistance, and Immunosuppression in Pan-Cancer

Abstract: BackgroundJMJD8 has recently been identified as a cancer-related gene, but current studies provide limited information. We aimed to clarify its roles and the potential mechanisms in pan-cancer.MethodsPan-cancer bulk sequencing data and online web tools were applied to analyze JMJD8’s correlations with prognosis, genome instability, cancer stemness, DNA repair, and immune infiltration. Moreover, single-cell datasets, SpatialDB database, and multiple fluorescence staining were used to validate the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Based on our research results, we have made some bold speculations, such as RARA-AS1-induced T cells follicular helper cells in GBM to participate in immune responses, and RARA-AS1-promoted Macrophages M2 infiltration in LUAD to participate in immune responses. In previous studies, correlation analysis was also applied, and the gene JMJD8 was found to be highly correlated with M2 macrophages, confirming its potential as a therapeutic target 31 .…”
Section: Discussionmentioning
confidence: 79%
“…Based on our research results, we have made some bold speculations, such as RARA-AS1-induced T cells follicular helper cells in GBM to participate in immune responses, and RARA-AS1-promoted Macrophages M2 infiltration in LUAD to participate in immune responses. In previous studies, correlation analysis was also applied, and the gene JMJD8 was found to be highly correlated with M2 macrophages, confirming its potential as a therapeutic target 31 .…”
Section: Discussionmentioning
confidence: 79%
“…We extracted expression data for immune checkpoint components (inhibitory and stimulatory) and several PCD (pyroptosis, cuproptosis, anoikis, necroptosis, disulfdptosis and autophagy) markers and evaluated the association of MCM3 expression with these markers. The correlation of MCM3 with 5 MMR signatures and 44 RNA modification genes (m1A, m5C and m6A) in pan-cancer was analysed ( Liang et al, 2022 ). In addition, we obtained pan-cancer differentially methylated probe-based stemness index (DMPsi) from the study by Malta et al to determine the relationship between MCM3 expression and cancer stemness ( Malta et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…It can still be predicted in the absence of homologous templates. As previously reported ( Liang et al, 2022 ), using the default parameters of Alphafold2 to predict the structure of KRIT1 wild-type and mutant proteins, the optimal model was selected and obtained the protein data bank (PDB) files of the three-dimensional structure of KRIT1 protein. Meanwhile, to visualize the mutant and wild-type KRIT1 protein structures, the predicted PDB files were imported into Swiss-PDB Viewer (Version 4.0.4) for protein structure drawing.…”
Section: Methodsmentioning
confidence: 99%